Pengaruh dividen, ukuran perusahaan, hutang jangka panjang, earning volatility, pertumbuhan aset, trading volume, dan kepemilikan manajerial terhadap volatilitas harga saham - PRISKILLA THERESIA; ERIKA JIMENA ARILYN (Jurnal Bisnis dan Akuntansi, 2015)
The purpose of this research is to test and investigate the influence of dividend yield, dividend payout ratio, firm size, long term debt, earnings volatility, growth asset, trading volume, and managerial ownership to stock price volatility. The population of this research is Basic and Chemical Industry Listed in Indonesia Stock Exchange over the 4 years period 2010-2013. Sample consists of 14 companies, selected using purposive sampling method. Data was analyzed using Panel Data Regression Analysis The result shows that dividend yield, dividend payout ratio, firm size, long term debt, earnings volatility, growth asset, trading volume, and managerial ownership influence stock price volatility simultaneously. Partially, only firm size influences on stock price volatility.